Gender, power and sexuality among youth on the streets of Durban: Socio-economic realities. (July 2014) - Osthus, Ingrid Scharer; Sewpaul, Vishantie
This article is based on a qualitative study on sexuality, identity and relationships among female and male youth living on the streets. Data were obtained from approximately 50 focus groups and individual interviews with 37 youth, of which 17 were female. There were several themes with regard to masculinity and femininity and constructions of motherhood and fatherhood that emerged from the study. In this article we focus on the following broad theme: men as providers, violence, sex, and sexuality. Recommendations are made regarding consciousness raising, therapeutic intervention, transforming gendered relationships and working towards socio-economic equality.